Application of rapid test kits for the determination of Diarrhetic Shellfish Poisoning (DSP) toxins in bivalve molluscs from Great Britain. (1st March 2016) - Johnson, Sarah; Harrison, Keith; Turner, Andrew D.
Abstract: Four commercial rapid screening methods for Diarrhetic Shellfish Poisoning were applied to the analysis of naturally contaminated shellfish samples from GB. The performance of each kit was assessed through comparison with the reference LC-MS/MS method on a range of both positive and negative bivalve mollusc samples. A quantitative PP2A protein phosphatase assay was the only assay to show the complete absence of false negative results. It showed a fair correlation with LC-MS/MS but with an overall overestimation of sample toxicity together with some indications of interference from sample matrix, most notably within oyster species. A quantitative competitive ELISA also gave a fair correlation with LC-MS/MS, with no evidence of toxicity overestimation and with a good response to samples containing little or no DST's, although one false negative was recorded. The two qualitative lateral flow assays both provided a high percentage agreement with the LC-MS/MS results and there were no indications of false positive results, although both kits also returned one false negative result. The false negative results returned by the three assays were all associated with samples containing high proportions of DTX2, a toxin which occurs commonly in UK shellfish. The scanners provided with both lateral flow assays were easy to use and the provision of numerical results enables a semi-quantitative assessment of toxicities which would significantly benefit the end user. Whilst key differences exist between the proposed assays they are all rapid, do not require expensive equipment and the work here has provided some evidence for suitability for indicative testing for some species of bivalve shellfish from GB. Further work is required however using a larger number of test kit batches on a greater number of samples, particularly for those containing high proportions of DTX2. Highlights: DSP toxins in Great Britain. Application of immunochromatography. ELISA test kits. Comparison of rapid methods. Issues with DTX2 toxin.